IMPLEMENTASI KEBIJAKAN TAMBAHAN PENGHASILAN PEGAWAI DALAM MINGKATKAN KINERJA PEGAWAI MELALUI LAPORAN KINERJA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA TOMOHON - Muslianto, Udiyarti; Mingkid, Elfie; Waleleng, Grace Jane (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to determine and understand the results of the Implementation of Employee Income Supplement Policy in Improving Employee Performance Through Performance Reports at the Tomohon City Human Resources Staffing and Development Agency and to find out the problems and solutions used in overcoming the problems that occur. This type of research is descriptive qualitative research. Data collection methods are carried out by triangulation (combined), and are inductive. The use of qualitative research methods is due to the fact that in analyzing the results of the research is descriptive or describing with interview measurement tools. In general, the results of this research are as follows: The implementation of the Employee Income Supplement policy in improving employee performance through performance reports at BKPSDM Tomohon City has not been effective, this is based on the results of the study it can be seen that of the 5 aspects of employee performance assessment, namely service orientation, integrity, commitment, cooperation, work discipline, only integrity, commitment, and cooperation, which get good ratings, while aspects of service orientation and discipline get sufficient ratings, meaning that employee performance in terms of service orientation and work discipline is still low and needs to be further improved.